2011
DOI: 10.54552/v72i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Flow Streamlining for Cooling Improvement in Ventilated Brake Disc Using CFD as Design Tool

Abstract: This paper presents experimental and Computational Fluids Dynamics (CFD) investigations of the flow and heat transfer in ventilated brake discs. The validation CFD model is done using the straight blade (baseline design) configuration with available experimental data. Development of an experiment rig with basic measuring devices and uncertainty calculation are discussed. Then, unidirectional racing blade configuration is then further focused on the improvement of the brake cooling using the similar numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…From Computational Fluid Dynamics (CFD) simulations, the heat transfer rates increase linearly with the rotational speed. 15 Wallis et al compared the thermal performance of three types of brake discs: straight radial vanes (SRV), SRV with rounded edges (SRV-R), and diamond and tear-drop pillars (DTDP). It was found that whilst the heat transfer capabilities of the SRV-R and DTDP rotor are similar, the airflow rate through the DTDP passages is approximately 12% lower than the flow rate through the SRV-R passages.…”
Section: Introductionmentioning
confidence: 99%
“…From Computational Fluid Dynamics (CFD) simulations, the heat transfer rates increase linearly with the rotational speed. 15 Wallis et al compared the thermal performance of three types of brake discs: straight radial vanes (SRV), SRV with rounded edges (SRV-R), and diamond and tear-drop pillars (DTDP). It was found that whilst the heat transfer capabilities of the SRV-R and DTDP rotor are similar, the airflow rate through the DTDP passages is approximately 12% lower than the flow rate through the SRV-R passages.…”
Section: Introductionmentioning
confidence: 99%